Knowledge Intensive Business Services in Regional Systems of Innovation - Initial Results from the Case of Southeast-Finland - Thorsten Bohn (European Regional Science Association (ERSA), 2003)
Within innovation systems, it is not only the creation of knowledge that counts but the flow of such knowledge from the producer to the user. Therefore, a huge national knowledge base does not necessarily guarantee intensive innovation activities. Instead, the distribution power within national innovation systems is important. In the process of distributing knowledge that is relevant for innovations, different actors can be identified. Besides organisations that have been put up by (regional) governments like technology transfer institutes, technology parks etc., one major group of actors are so called knowledge intensive business services (KIBS). It is believed that they hold a decisive role in the creation and diffusion of knowledge within regional systems of innovation, since they can take up a bridging function between knowledge suppliers and knowledge users. Research so far has focused mainly on the role of so-called technology-based KIBS for high-tech industries (e.g. ICT). The role and significance of non-technology KIBS (like business consulting, legal services etc.) on the other hand has been neglected, although they can have a decisive effect on the strategical direction of innovations. Since most of the KIBS-research has focused on KIBS in highly developed innovation systems and metropolitan areas, there is not very much known about the role and significance of KIBS in more peripherical and rural regions, although it is an interesting question if KIBS in these regions play the same role in their clients innovation processes and if they are able to introduce new knowledge from outside the regions. The proposed paper deals with the role and significance of knowledge intensive business services in the creation and diffusion of knowledge and their role in the development of peripherical regions. It sheds some light on the changing environment for KIBS and the change in the structure of KIBS in peripherical regions. Furthermore, it deals with the specific role of KIBS for the transfer of knowledge from outside the region and their ability to link sources of knowledge from different industries. The proposed paper is based on the systems of innovation approach. It uses data obtained by a standardised questionnaire that was sent to all relevant KIBS firms in Southeast-Finland during 2002. Furthermore, the results of about 50 interviews with KIBS, the clients of KIBS and relevant institutional actors in Southeast-Finland are being used. Based on the previously mentioned data, the paper suggests that the dichitomy between technology-KIBS and non-technology KIBS is not appropriate in many cases, since most KIBS firms provide a mixture of services. The paper suggests that KIBS hold an important position for the diffusion of knowledge that is needed for innovations even in more or less low-tech industries. This is especially true for knowledge that comes from outside the region. The paper also shows the relative importance of different channels for the distribution of knowledge within the innovation system. However, the paper suggests that for the observed region the power of KIBS in linking different industries is rather limited.
Keywords: 330